The ghosts of bigotry;: six lectures - Yorke, P. C. (The Text book publishing co., 1913)
Ghosts in general.-- The gunpowder plot.-- The popish plot.-- The Gordon riot.-- The ecclesiastical titles bill.-- Anti-Catholic movements in North America.